Future of India: politics, economics and governance - Jalan, Bimal (New delhi, 2005)
In The Future of India: Politics, Economics and Governance, Bimal Jalan, former governor of the Reserve Bank of India, takes up the formidable challenge of examining the nuts and bolts of this proposition. In his thought-provoking, clear-sighted analysis, he argues that the key factors to success are three: politics, economics and governance. It is the interface between these, and their combined effect on the functioning of our democracy, which will largely determine India's future. An understanding of this interface will help explain the swings in India's political and economic fortunes over the past decades, and why the promise has been belied.
Keywords: India-Governance